A Place Called Bowles’s: In Search of a Historic Site from the War of 1812 - St-Denis, Guy (Ontario History, 2019)
General Henry Procter’s ignominious retreat at the Battle of Moraviantown in 1813 ruined his reputation. At his court martial, a number of pioneer place names were identified as milestones in his retreat, including a homestead called Bowles’s an important depot for the British where two schooners were scuttled to prevent the Americans from advancing up the Thames River by boat. This article uses evidence from a variety of original sources to determine the most likely location of Bowles’s homestead and, perhaps, two historic shipwrecks from the War of 1812.